Alma M. Karlin's Visits to Temples and Shrines in Japan - Shigemori Bučar, Chikako (Poligrafi, 2019)
Alma Maximiliana Karlin (1889 - 1950), born in Celje, went on a journey around the world between 1919 and 1928, and stayed in Japan for a little more than a year, from June 1922 to July 1923. There is a large collection of postcards which she used and brought back to Slovenia, presently archived in the Regional Museum of Celje. Among them there is quite a number of postcards from Japan (528 pieces), and those of temples and shrines, including tombs of emperors and other historical persons, amount to 100. Alma almost always wrote on the reverse of these postcards some lines of explanation about each picture in German. On the other hand, the Japanese part of her travelogue is very short, only about 40 pages of 700 pages in two volumes. (Einsame Weltreise / Im Banne der Südsee). In order to understand Alma Karlin’s observation and interpretation of things related to religions in Japan and beliefs of Japanese people, we depend on her memos on the picture postcards and her rather subjective pieces of impressions in her travelogue. This paper presents facts on the religious sights which Alma visited, and analysis of Alma’s understanding and interpretation of the Japanese religious life.